Russell and Chomsky as Advocates of Humanistic Education - Woodhouse, Howard (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2020)
This article shows how Bertrand Russell and Noam Chomsky’s approaches to humanistic education are grounded in the concepts of growth, knowledge, language, freedom, and social justice. Despite their epistemological differences, Russell and Chomsky agree on the need for educating the public to abuses of power. Their own practice of education is a source of inspiration for intellectuals, who wish to counter the current discourse in schools and universities by upholding the value of academic freedom.